Simple approach for the preparation of 15−15N2-enriched water for nitrogen fixation assessments: evaluation, application and recommendations - Klawonn, Isabell; Lavik, Gaute; Böning, Philipp; Marchant, Hannah; Dekaezemacker, Julien; Mohr, Wiebke; Ploug, Helle (Frontiers in Microbiology, 2015)
Recent findings revealed that the commonly used 15N2 tracer assay for the determination of dinitrogen (N2) fixation can underestimate the activity of aquatic N2-fixing organisms. Therefore, a modification to the method using pre-prepared 15−15N2-enriched water was proposed. Here, we present a rigorous assessment and outline a simple procedure for the preparation of 15−15N2-enriched water. We recommend to fill sterile-filtered water into serum bottles and to add 15−15N2 gas to the water in amounts exceeding the standard N2 solubility, followed by vigorous agitation (vortex mixing ≥ 5 min). Optionally, water can be degassed at low-pressure (≥950 mbar) for 10 min prior to the 15−15N2 gas addition to indirectly enhance the 15−15N2 concentration. This preparation of 15−15N2-enriched water can be done within 1 h using standard laboratory equipment. The final 15N-atom% excess was 5% after replacing 2–5% of the incubation volume with 15−15N2-enriched water. Notably, the addition of 15−15N2-enriched water can alter levels of trace elements in the incubation water due to the contact of 15−15N2-enriched water with glass, plastic and rubber ware. In our tests, levels of trace elements (Fe, P, Mn, Mo, Cu, Zn) increased by up to 0.1 nmol L−1 in the final incubation volume, which may bias rate measurements in regions where N2 fixation is limited by trace elements. For these regions, we tested an alternative way to enrich water with 15−15N2. The 15−15N2 was injected as a bubble directly to the incubation water, followed by gentle shaking. Immediately thereafter, the bubble was replaced with water to stop the 15−15N2 equilibration. This approach achieved a 15N-atom% excess of 6.6 ± 1.7% when adding 2 mL 15−15N2 per liter of incubation water. The herein presented methodological tests offer guidelines for the 15N2 tracer assay and thus, are crucial to circumvent methodological draw-backs for future N2 fixation assessments.